New reductive rearrangement of N-arylindoles triggered by the Grubbs–Stoltz reagent Et3SiH/KOtBu. Issue 14 (20th March 2020) - Smith, Andrew J.; Dimitrova, Daniela; Arokianathar, Jude N.; Kolodziejczak, Krystian; Young, Allan; Allison, Mark; Poole, Darren L.; Leach, Stuart G.; Parkinson, John A.; Tuttle, Tell; Murphy, John A.
Abstract : N -Arylindoles are transformed into dihydroacridines in a new type of rearrangement, through heating with triethylsilane and potassium tert- butoxide. Abstract : N -Arylindoles are transformed into dihydroacridines in a new type of rearrangement, through heating with triethylsilane and potassium tert- butoxide. Studies indicate that the pathway involves (i) the formation of indole radical anions followed by fragmentation of the indole C2–N bond, and (ii) a ring-closing reaction that follows a potassium-ion dependent hydrogen atom transfer step. Unexpected behaviors of 'radical-trap' substrates prove very helpful in framing the proposed mechanism.